2016
DOI: 10.1155/2016/8631381
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Tumour Staging with Endorectal Ultrasound: Is There Any Difference between Western and Eastern European Countries?

Abstract: Background. Rectal tumour management depends highly on locoregional extension. Rectal endoscopic ultrasound (ERUS) is a good alternative to computed tomography and magnetic resonance imaging. However, in Hungary only a small amount of rectal tumours is examined with ERUS. Methods. Our retrospective study (2006–2012) evaluates the diagnostic accuracy of ERUS and compares the results, the first data from Central Europe, with those from Western Europe. The effect of neoadjuvant therapy, rectal probe type, and inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
4
0
3
Order By: Relevance
“…In fact, RT is given more commonly among rectal cancer patients than colon cancer patients, and there are variations in the type and sequence of surgery. 34 Thus, the true effect of RT on survival rates may be influenced by the tumor location. To eliminate the confounding effect of tumor location, we examined the OS and CSS rates overall as well as among colon and rectal cancers separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, RT is given more commonly among rectal cancer patients than colon cancer patients, and there are variations in the type and sequence of surgery. 34 Thus, the true effect of RT on survival rates may be influenced by the tumor location. To eliminate the confounding effect of tumor location, we examined the OS and CSS rates overall as well as among colon and rectal cancers separately.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous literature, RT, age, sex, tumor location, grade, AJCC T, N, and M categories, and chemotherapy were considered as study prognostic factors in this study. 6,13,18,[28][29][30][31][32][33][34][35][36] All variables used in the study were dichotomized. Radiotherapy was considered as the main exposure variable, with nodal category (N1c versus N0) as the secondary exposure variable.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Flexible echoendoscopes may be advanced under visual control up to the level of the tumor and are able to pass through narrower lumens of stenosing tumors. Comparative studies between the 2 types of devices are currently limited and have shown contradictory results for rectal cancer staging 4 5 6 . Both types of probes (rigid and flexible) do have the possibility of examining the iliac lymph nodes at about 20–25 cm from the anal verge.…”
Section: Endorectal Ultrasoundmentioning
confidence: 99%
“…Therefore, both EUS and EUS-RTE are a good choice for diagnosis, especially in the case of mild and moderate rectal malignancies. For the staging of advanced lesions, other methods with higher sensitivity such as MRI are recommended [ 11 ]. The data and images obtained by SR-RTE can be considered complementary information obtained by conventional EUS [ 12 ].…”
Section: Discussionmentioning
confidence: 99%